RESEARCH ON FATIGUE CRACK PROPAGATION LIFE OF CASTING CRANE GIRDER UNDER IMPACT LOAD - XIANG ZaiYu; XIAO ZhengMing; WU Xing; GAO XiangYuan; WANG Xin (Jixie qiangdu)
Casting crane is widely used as hoisting and conveying equipment in the metallurgical industry. The bad and failure working environment caused remarkable accident harm,so mechanical properties and fatigue analysis accurately on this equipment seem very important. Establishing bridge’s 3D model and dynamic model reasonably for the 200 /63 t crane which made up by four beams,runways and double trolley. Base on the actual load characteristics and dynamic parameter analysis,and finishing the transient dynamic analysis in the ANSYS software for the bridge crane through structure simplify reasonably and boundary conditions. On the basis of obtaining accurate stress dynamic response with the dangerous girder structure,and then combine with the theory of linear elastic fracture mechanics theory,addressing the fatigue crack propagation life of beans under impact load. This study provide the theory basis for the structure optimization and reliability design of crane.